2013
DOI: 10.1016/j.molonc.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

p27kip1 maintains a subset of leukemia stem cells in the quiescent state in murine MLL‐leukemia

Abstract: MLL (mixed-lineage leukemia)-fusion genes induce the development of leukemia through deregulation of normal MLL target genes, such as HOXA9 and MEIS1. Both HOXA9 and MEIS1 are required for MLL-fusion gene-induced leukemogenesis. Co-expression of HOXA9 and MEIS1 induces acute myeloid leukemia (AML) similar to that seen in mice in which MLL-fusion genes are over-expressed. p27kip1 (p27 hereafter), a negative regulator of the cell cycle, has also been defined as an MLL target, the expression of which is up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…3b). The undifferentiated CD117 + CD11B low population 35 was significantly reduced in both RIP1 −/− and RIP3 −/− AML cells compared to WT AML cells. Both RIP1 −/− and RIP3 −/− AML cells express increased levels of the differentiation marker CD11b compared to WT AML cells (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…3b). The undifferentiated CD117 + CD11B low population 35 was significantly reduced in both RIP1 −/− and RIP3 −/− AML cells compared to WT AML cells. Both RIP1 −/− and RIP3 −/− AML cells express increased levels of the differentiation marker CD11b compared to WT AML cells (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Is this a necessity or simply an unwanted byproduct? In favor of the first scenario, it has been suggested that low level of p27 induction by MLL-fusion proteins might prevent leukemia initiating cells from exhaustion (Zhang et al, 2013). In favor of the second scenario, MLL-fusions unavoidably acquire this context-dependent tumor suppressor activity through the common MLL amino-terminus.…”
Section: Discussionmentioning
confidence: 99%
“…This indicate the possibility of a phenotypic inter-convertibility between CD117 + CD11b hi and CD117 + CD11b lo MA9 leukemic cells. 12 The above phenomenon appears to have also occurred in MT1 cells.…”
mentioning
confidence: 90%